Fatores críticos da competitividade da cadeia produtiva da carne bovina do estado de São Paulo - Rosa, Fabiano Ribeiro Tito (2009)
Brazil is the main player in the beef world market. Among Brazilian States, Sao Paulo is in the first position in terms of exportation and second position in terms of production. However, the market share of the state has been decreasing, and larger investments are taking place in the Center-North region of the country. Through a survey of statistics and interviews with beef experts, this study identified the critical aspects of the competitiveness of the beef agri-chain in the State of Sao Paulo. In comparison with domestic competitors (other States), the limited supply of resources and inputs (areas of pasture, livestock and grains), the comparatively high costs of production and the tax between States ( war tax ) adversely affect the competitiveness of the beef agri-chain in the State of Sao Paulo. The conditions of the logistic and infrastructure, the access to production technology and the level of firms management are favorable factors for the Sao Paulo competitiveness. In comparison with foreign competitors, some factors that were unfavorable the supply of resources/inputs and the costs of production began to positively affect the competitiveness of the state. In another hand, the level of technology and management, for example, now began to negatively affect the results of this beef agri-chain. Food safety deserves special attention, because Brazil health status (including São Paulo) prevent the access of Brazilian in natura beef to more than a half of the world market. The actions to increase the competitiveness of the beef agri-chain of São Paulo must act in order to: minimize the tax cost for the entry of raw materials (grain and livestock) in the state, reduce risk and improve the health status of the state; maximize the logistical and infrastructural advantages of the State (the experts that were interviewed showed the need for improvements in the port of Santos) and allocate resources to areas of R&D that seek, among the industries, the development of products with higher added value and, among the producers, new technologies to enhance economic and technical efficiency of intensive production (new use of the waste, optimizing the use of machinery, crop-livestock integration and implementation of management systems, for example).